2022
DOI: 10.1088/1748-9326/ac54ca
|View full text |Cite
|
Sign up to set email alerts
|

Power law scaling and country-level centralization of global agricultural production and trade

Abstract: Global food production and international trade are rapidly expanding and drive increasing agricultural globalization and specialization. Following production patterns, network properties and added-value chains, exportable surpluses of countries can offset food and feed deficits in other countries. However, production and trade patterns are barely addressed in the scientific literature as two interactive components of global agriculture. Integrated analysis of the temporal dynamics and distribution patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…However, along with worldwide increases in personal income, population, and living conditions improvements, demands for agricultural products (meat in particular) have been growing, of which bovine meat (cattle and buffalo) from 2000 to 2018 increased monotonically by 21.7% (). Given the constraints in resources and environmental capacities, such growing meat demands and productions cannot be met in many countries and regions. , As an alternative, the international food trade provides an essential engine for the speedup of global food production. Growth in all crop sectors and livestock production is associated with rising costs, increasing resource constraints, and environmental pressures . It is not a sustainable way to expand or convert vegetation lands and wetlands to croplands because this would otherwise increase greenhouse gas (GHG) emissions via declining carbon sinks and cause the loss of biodiversity and aggravation of sensitive ecosystems. , Under different climates, water and land resources and agricultural productivity differ in different places and countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, along with worldwide increases in personal income, population, and living conditions improvements, demands for agricultural products (meat in particular) have been growing, of which bovine meat (cattle and buffalo) from 2000 to 2018 increased monotonically by 21.7% (). Given the constraints in resources and environmental capacities, such growing meat demands and productions cannot be met in many countries and regions. , As an alternative, the international food trade provides an essential engine for the speedup of global food production. Growth in all crop sectors and livestock production is associated with rising costs, increasing resource constraints, and environmental pressures . It is not a sustainable way to expand or convert vegetation lands and wetlands to croplands because this would otherwise increase greenhouse gas (GHG) emissions via declining carbon sinks and cause the loss of biodiversity and aggravation of sensitive ecosystems. , Under different climates, water and land resources and agricultural productivity differ in different places and countries.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the focus has been mainly on producers and/or consumers. However, intermediary trading of agricultural commodities is fastly growing globally, which is centralized among a few countries 13 . In summary, Li and colleagues 7 have shown that food transport emissions matter for climate action more than previously thought.…”
mentioning
confidence: 99%
“…Aside from these chokepoints, the stability and resilience of the global trade network is likely to be strongly conditioned by the structure of the network (Albert and Barabási, 2000). Dupas et al's (2022) analysis of the trade between 1986 and 2016 in cereals, oil crops, meat, fruits, vegetables, coffee, and cocoa found that production and trade are highly centralised among a small number of countries. Ultimately, this leaves a growing number of netimporting countries sourcing from a decreasing number of top-producing countries, increasing their vulnerability to supply shocks.…”
Section: Agricultural Production and Trade In A Climate Contextmentioning
confidence: 99%